PENGARUH MOTIVASI DAN DISIPLIN TERHADAP KINERJA KARYAWAN BMT KHAIRUL AMIN MARTAPURA - Bahriah Bahriah; Lola Malihah; Nur Habibah (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2023)
Improving employee performance is one of the goals of the organization. The success and performance of employees is determined by many factors including motivation, discipline, leadership, work atmosphere and so on. This study aims to find out whether motivation and discipline affect the performance of BMT Khairul Amin Martapura employees. The variables in this study are Motivation (X1) and Discipline (X2), bound variables: Employee Performance (Y). This research is a field research with a quantitative approach. The samples in this study used saturated samples. Data collection techniques are carried out by the distribution of questionnaires and documentation.. The results showed that simultaneously there was a positive and significant influence on the performance of BMT Khairul Amin Martapura employees. This is evidenced from the value of Sig. = 0.001 < α = 0.1 and the value of Fhitung = 10.837 > Ftabel = 2.62. Then H0 is rejected and H1 is accepted, while partially obtained the result that the motivation variable has a positive and insignificant effect, where the value of Sig. = 0.814 > α = 0.1 and the calculated value = 0.240 < ttabel = 1.740. Disciplinary variables have a positive and significant effect, where the value of Sig. = 0.002 < α = 0.1 and the value of counting = 3.741 > ttabel = 1.740. The coefficient of determination test shows that motivation and discipline simultaneously affect employee performance by 56.1%.